Distinguishing shallow from mid-crustal magmatic processes at Soufrière Hills Volcano using Finite Element Modelling and co-analysis of EDM and GPS data - Johnson, Alexander; Hickey, James; Pascal, Karen; Williamson, Ben; Syers, Raquel (Volcanica, 2023)
We modelled ground deformation at Soufrière Hills Volcano (SHV), using data collected by the Montserrat Volcano Observatory from 2010–2019. We investigate the combined use of Electronic Distance Measuring (EDM) and Global Positioning System (GPS) to distinguish shallow from mid-crustal magmatic processes and their surface deformation profiles. Our results suggest that the EDM network responds predominantly to changes in the shallow magmatic system, whereas GPS records variation at mid-crustal levels. In addition, we show that the behaviour of the EDM network, and of the GPS site HERM, can be explained by underpressurisation in a shallow dyke conduit orientated NNW–SSE, while the mid-crustal system was still undergoing pressurisation. The modelled dyke may be responding to magma cooling and contraction associated with a previous intrusion. We find that geodetic monitoring coverage of multiple flanks within 1 km of the vent can improve our understanding of shallow magmatic system processes with asymmetric deformation fields.